Biological landmark Vs quasi-landmarks for 3D face recognition and gender classification - Hawraa H. Abbas; Ammar A. Altameemi; Hameed R. Farhan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Face recognition and gender classification are vital topics in the field of computer graphic and pattern recognition. We utilized ideas from two growing ideas in computer vision, which are biological landmarks and quasi-landmarks (dense mesh) to propose a novel approach to compare their performance in face recognition and gender classification. The experimental work is conducted on FRRGv2 dataset and acquired 98% and 94% face recognition accuracies using the quasi and biological landmarks respectively. The gender classification accuracies are 92% for quasi-landmarks and 90% for biological landmarks.